NILAI-NILAI RELIGIUS DALAM TARI SINOMAN HADRAH DI DESA PULANTAN KECAMATAN ALUH-ALUH KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Suwarjiya; Dewi Rukmini (Yayasan Pendidikan Literasi Borneo, 2025)
This study aims to uncover and analyze the religious values ​​inherent in the Sinoman Hadrah Dance in Pulantan Village, Aluh-Aluh District, Banjar Regency, South Kalimantan Province. As a local traditional art form that developed through the acculturation of Arab-Malay culture, Sinoman Hadrah plays a role beyond mere entertainment—it becomes a medium for preaching, spirituality, and education of Islamic values ​​through elements of poetry, movement, music, and other religious fastings. The research method used is descriptive qualitative, with a phenomenological approach; Data collection was conducted through field observations, interviews, and document analysis—then analyzed thematically. The results of the study indicate that this dance is imbued with religious values ​​such as faith, sharia, and morals, particularly through the recitation of poetry and praise of Allah and the Prophet Muhammad (peace be upon him). It also serves as a medium for preaching and education in Islamic values ​​(living the sunnah). This dance tradition not only strengthens Banjar cultural identity but also strengthens social ties and the spirituality of its community. Thus, the Sinoman Hadrah Dance in Pulantan Village can be said to serve as a means of religious expression, moral education, and the sowing of Islamic values ​​in the dynamics of Banjar community life.